Analysis of the Working Capital Management Effects on Profitability (Case Study of Property and Real Estate Companies Listed in OSIRIS Year 2017-2021) - Juita Tiur Napitupulu; Moch. Doddy Ariefianto (PT Mattawang Mediatama Solution, 2023)
This study aims to determine the effect of working capital, receivable turnover, and inventory turnover on profitability in property companies listed on OSIRIS for 2017-2021. This type of research used quantitative methods. The data collection method employed the literature study and the documentation methods. The sampling technique was a purposive sampling of 30 companies. The research subjects involved Manufacturing Companies in the Property & Real Estate Sector listed in OSIRIS for the 2017-2021. The study's results indicated an effect of working capital, receivable turnover, and inventory turnover on profitability in property companies listed in OSIRIS year 2017-2021.